Electrochemiluminescent method for polyacenes detection using semiconductor quantum dots - Sushko, O. A. (B. Verkin Institute of Low Temperature Physics and Engineering, NASU, 2017)
There are known methods for PAHs detection, such as chromatography, immuno-chemistry, biological and chemical ones. However, they have several disadvantages, including high cost, duration and complexity of the analysis procedure, the high detection limit and low selectivity. Therefore, a well-proven electrochemiluminescence method of PAH reduction was used in combination with modern technologies, such as nanotechnology and nanomaterials.
Keywords: polyacenes; quantum dots; electrochemiluminescent method